Implementation of Reinforced Concrete Floor Beams and Plates in a 5-Storey Hospital Building Construction Project - Rosiyani, Tissa Rahayu; Kristiawan, Agung; Suwandi, Putri Anggi Permata (Science and Technology Research Centre, Universitas PGRI Semarang, 2025)
Hospitals are health care institutions that provide a full range of individual health services and provide inpatient, outpatient and emergency services. The comprehensive health services referred to in this case include promotive, preventive, curative and rehabilitative.[1] The construction of the new building at PKU Muhammadiyah Blora Hospital will be the center of the physiotherapy clinic, pharmaceutical satellite, commercial area, drop off, ICU, inpatient, office. The existence of the new building is a step to improve the quality of health services for patients. The new hospital building is located to the east of the main building in the PKU Muhammadiyah Blora Hospital complex. The work observed is the work of beams and reinforced concrete floor slabs. This work has several steps of workmanship. The work on the beams and floor slabs must complete the reinforcement and formwork simultaneously first, then the casting can be done.